Communication management in the sister village program: Mount Merapi disaster mitigation efforts with a participatory approach - Yani Tri Wijayanti; S Bekti Istiyanto; Tri Susanto; Handini Handini; Irwanto Irwanto (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2024)
The 2010 eruption of Mount Merapi led the Disaster Management Agency (BPBD) of Magelang Regency to implement the Sister Village Program as a participatory disaster mitigation strategy. This study aims to examine how communication was managed to support this initiative, focusing on audience identification, goal setting, message planning, and channel selection. Using a qualitative case study approach, data were collected through participatory observation and in-depth interviews with BPBD officials, village leaders, and residents from both disaster-prone and buffer villages. Findings show that the integration of local knowledge, structured dialog through the three plano papers, and inclusive stakeholder engagement played a critical role in enhancing preparedness and response. The study highlights that communication strategies rooted in community-driven practices foster trust, coordination, and timely evacuation. These results suggest that participatory communication management is essential for effective disaster mitigation and should be adapted to other disaster-prone areas in Indonesia.